Numerical Modeling in the Structural Study of Technogenic Rock Array; Geotechnical and Geological Engineering; Vol. 36, iss. 4 - Tyulenev M. A. Maksim Anatolievich; Markov S. O. Sergey Olegovich; Gasanov M. A. Magerram Ali Ogly; Zhironkin S. A. Sergey Aleksandrovich (2018, 2018)
Title screen